Conversion of oil palm trunk to sugars and organic acids by sub-critical water reaction - Ishak, Hazwani (2018)
Oil palm trunk (OPT) aging more than 25 years is among the most abundant biomass producing millions of tonnes of OPT per year. These abandoned OPT are either felled and chipped to allow for quicker return of nutrients to the soil or killed with poison allow it to decompose naturally in the field. OPT is a bio resource that has a high potential for conversion to energy and value added products. Sub-critical water (sub-CW) has been gaining interest in the conversion of biomass to useful products and energy due to its unique features. The objectives for this study are to convert OPT into sugars and organic acids by subcritical water reaction, to determine the optimum time and temperature to produce maximum amount of sugars, and to study the decomposition of pure cellulose by sub-CW reaction and compare with the results of OPT. Two different ages of 21- and 35-year-old OPTs were used to choose the best OPT that produce high yield of sugar. Both OPTs were divided into top and bottom parts whereby the inner zone were used since it contain high moisture content. A reactor filled with OPTs and distilled water was immersed in oil or molten salt baths for the sub-CW reaction. The reaction was carried out at temperatures ranging between 100 and 370°C and reaction time from 1 to 20 min. The results revealed that the 21-year-old (OPT 21) produced the maximum yield of sugar and organic acids. The optimum conditions for the highest yield of total sugar were 0.41 kg/kg-dry OPT (240 °C, 5 min) and 0.77 kg/kg-dry OPT (220 °C, 5 min) in bottom and top part, respectively. Sub-CW treatment caused the hydrolysis to occur thus promoted the decomposition of hemicellulose and cellulose in OPT. The saccharides produced as a result of the hydrolysis of OPT21 were cellotriose, cellobiose, glucose, fructose, and xylose. In the bottom part, fructose has the highest yield of 0.099 kg/kg-dry OPT at 220 °C while in top part, glucose has the highest yield of 0.51 kg/kg dry OPT at 230 °C. Sugar degradation of OPT produced organic acids such as acetic acid, lactic acid and malic acid. Acetic acid produced the highest yield of 0.2 kg/kg-dry OPT and 0.16 kg/kg- dry OPT in bottom and top parts, respectively. The decomposition of pure cellulose by sub-CW reaction successfully explained that hydrolysis had occurred. Sub-CW reaction showed promising results in producing sugars and organic acids from decomposition of waste OPT. The sugar yields from OPT by sub-CW can be further study to produce second generation of bioethanol as alternative in replacing fossil fuels.